Comparative Evaluation of the Levels of Minerals and Mineral Safety Index of Raw, Roasted and Cooked Treculia Africana Seed Flours - Adesina, Adeolu Jonathan; Adeyeye, Emmanuel Ilesanmi (Journal of Food Science and Technology Nepal, 2016)
The raw, cooked and roasted seed parts of Treculia africana commonly called “afon” in Yoruba and “ukwa” in Ibo languages were investigated for the mineral composition using standard methods. Calculations of Ca/P, Na/K, [K/(Ca+Mg)], Ca/Mg ratios and mineral safety index were also carried out. In the mineral composition, raw samples were best in Na and K; roasted samples were highest in Ca and Mg; cooked samples were highest in Zn, Fe, Mn and P; in all the samples, Ca/P was generally lower than the 0.5 recommended for favourable absorption of calcium in the intestine for bone formation; the samples were all good in Na/K in that they were all lower than 0.6 recommended as the highest limit ratio that prevent high blood pressure; both the raw and processed samples were high in [K/(Ca+Mg)] and non of the sample type was good in Ca/Mg. In the mineral safety index (MSI) values: Fe with standard MSI of 6.7 recorded negative values of -3.20 and -4.20 in roasted seeds testa and cooked testa flours respectively whereas in all other sample parts positive values were recorded. The statistical analysis results (linear correlation) on a pair-wise comparison showed that the mineral contents in raw/roasted and raw/cooked were significantly different at ? = 0.05, df=n-1. The research has provided nutritional information with respect to processing methods on the minerals in the various parts of the seeds analyzed and that levels of nutritive minerals were more positively enhanced in the roasted seeds flour than in the cooked sample flours.